Pollen load and distribution on the body of Elaeidobius kamerunicus Faust. (Coleoptera: Curculionidae) within oil palm plantations - Van Basten Tambunan; Bandung Sahari; Damayanti Buchori; Purnama Hidayat (Perhimpunan Entomologi Indonesia, 2020)
The African oil palm weevil, Elaeidobius kamerunicus is an effective pollinator of oil palm. Each individual palm produces exclusively male or female inflorescence so that the success of pollination depends on the ability of the pollinator to transfer pollen from male to female flowers. The objective of this research was to study the amount of pollen carried by E. kamerunicus between male and female inflorescences (pollen load) and the amount of pollen carried on each part of the weevil’s body (pollen distribution). Fifty each of male and female E. kamerunicus individuals were collected from male and female flowers on trees in 3 locations: Siantar (North Sumatra), Dramaga (West Java), and Morowali (Central Sulawesi). Data on pollen load and pollen distribution on the weevil’s body were analyzed using ImageJ software. Results show that E. kamerunicus individuals collected more pollen from male flowers than from female flowers. In addition, male insects carried more pollen on their bodies than female insects. Pollen distribution on weevil body parts was highest on the elytra, followed by the thorax, abdomen, legs, and head respectively.